(untitled) - Grabowski, Ralph (New York, 2004)
Providing readers with the intermediate and advanced capabilities of AutoCAD® 2004, this book covers all functions and commands necessary for advanced drafting, as well as advanced features such as customizing, 3D design, externally referenced drawings, layouts, and AutoLISP®. Step-by-step tutorials and a logical order to the featured instruction make it easy for readers to use and apply AutoCAD and its commands. Discipline-specific information and tutorials in the areas of advanced drafting and three-dimensional design will appeal to a wide variety of readers’ interests.
Keywords: Autocad,Computer graphics